Pan Needs Private Sector Support - Sullivan, Nestor; Belgrave, Ian "Teddy" (Express)
In Part 3 of this four-part series, the authors argue that there need to be a more aggressive and enlightened intervention by the public and private sector if Trinidad and Tobago is to get its fair share of the benefits to be derived from development of the steelband process and the nationals of the country must play a leading role.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago